Analisis Kedisiplinan Siswa dalam Pembelajaran PAI Kelas V SD Pembangunan Laboratorium UNP - Nasution, Suryadi Ahmad; Ikhlas, Al- (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This research was conducted to analyze how students are disciplined in learning PAI in grade 5, including how students are disciplined in learning PAI, what are the factors that influence student discipline in learning PAI, as well as how teachers instill student discipline in learning PAI. The method used by researchers in this study is a qualitative method with a descriptive approach. This research was conducted at UNP Laboratory Development Elementary School. Data collection techniques that researchers use are observation, interviews, and documentation. The results of the study showed that the discipline of students in learning PAI in class V could not be said to be disciplined, because some students still violated disciplinary rules in the classroom and school regulations, among the indiscipline carried out by students, namely often being late for school, going in and out of class when learning is still going on, not doing homework, and not paying attention to learning. Factors that influence student discipline in learning PAI can be seen from 2 factors, namely internal factors there are some students whose interest and motivation are lacking in learning PAI in class V, then the environment where they live also has a bad effect on students. And the teacher's way of instilling student discipline in PAI learning is that the teacher pays less attention and rewords so that students are less enthusiastic about matters related to PAI learning, besides that the teacher also doesn'